Síndrome de Schmidt em paciente portador de Síndrome de Imunodeficiência Adquirida (SIDA): relato de um caso - Tibúrcin, Alberto Saraiva; Bazin, Anna Ricordi; Souza, Honomar Ferreira de; Azevedo, Kátia Martins Lopes de; Reis, Vera Lúcia Lopes dos (Brazilian Journal of Sexually Transmitted Diseases, 1994)
Schmidt's syndrome manifests itselfby adrenal insufficiency associated with others endocrine distrubs, most of ten liypotyreoidism. ln this paper we described an AIDS patient with signs and symptoms of adrenal insu:fficiency, hypogonadism, and subsclinical hypotyreoidism. We discuss the pathogenesis of this endocrine syndrome, and the diifficulties in diagnosing it in an AIDS patient, dueto the overlaping of clinicai findings.